Strategi Pengembangan Peran Pustakawan Dalam Pelayanan Perpustakaan Berbasis Inklusi Sosial - Agung Tri Dharma; Ely Sufianti; Nefi Aris Ambar Asmara (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
Libraries Social inclusion-based library transformation is an approach to library services that is committed to improving the quality of life and welfare of the library user community. The role of the librarian in the transformation program for library development to be more beneficial to the community is carried out by various strategies. The aim of the study is to analyze the role of librarians in library services based on social inclusion, analyze internal and external factors in developing the role of librarians in social inclusion-based library services, and formulate a strategy for developing the role of librarians in social inclusion-based library services at the Regional Library and Archives Service of West Java Province. The results showed that the development of the role of librarians in social inclusion-based library services has not been maximized, there are still people and users who do not know and utilize social inclusion-based library services. Utilization and strengthening of collaboration between users, the synergy team and the community is the strategy that is most likely to be carried out in the near future and the use of budget and policy stipulation is minimal.Keywords: librarians, library services, social inclusion, literacyABSTRAKPerpustakaan Transformasi perpustakaan berbasis inklusi sosial merupakan suatu pendekatan pelayanan perpustakaan yang berkomitmen meningkatkan kualitas hidup dan kesejahteraan masyarakat pengguna perpustakaan. Peran pustakawan dalam program transformasi pengembangan perpustakaan agar lebih bermanfaat bagi masyarakat dilakukan dengan berbagai strategi. Tujuan Penelitian menganalisis peran pustakawan dalam pelayanan perpustakaan berbasis inklusi sosial, menganalisis faktor-faktor internal dan eksternal pengembangan peran pustakawan dalam pelayanan perpustakaan berbasis inklusi sosial serta merumuskan strategi pengembangan peran pustakawan dalam pelayanan perpustakaan berbasis inklusi sosial di Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat. Hasil penelitian menunjukkan pengembangan peran pustakawan dalam pelayanan perpustakaan berbasis inklusi sosial belum maksimal, masih ada masyarakat dan pemustaka yang belum mengetahui dan memanfaatkan layanan perpustakaan berbasis inklusi sosial. Pemanfaatan dan penguatan kerjasama antar pemustaka, tim sinergi dan masyarakat merupakan strategi yang paling mungkin dilakukan dalam waktu dekat dan pengunaan anggaran maupun penetapan kebijakan yang lebih minim.